2010
DOI: 10.3758/app.72.6.1642
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vection by red

Abstract: We investigated the effects of colors on vection induction. Expanding optical flows during one's forward d self-motion were simulated by moving dots. The dots and the background were painted in equiluminant red and green. Experiments 1 and 2 showed that vection was weaker when the background was red than when the background was green. In addition, Experiment d 3 showed that vection was weaker when the moving dots were red than when the dots were green. Experiment k 4 demonstrated that red dots on a red backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
3
16
3
Order By: Relevance
“…which inhibit vection (Seno et al, 2010), and the farthest stimulus tends to dominate vection (Ohmi and Howard, 1988). These findings suggest that vection is modulated in a bottom-up fashion.…”
Section: Top-down and Bottom-up Modulations Of Vectionmentioning
confidence: 88%
“…which inhibit vection (Seno et al, 2010), and the farthest stimulus tends to dominate vection (Ohmi and Howard, 1988). These findings suggest that vection is modulated in a bottom-up fashion.…”
Section: Top-down and Bottom-up Modulations Of Vectionmentioning
confidence: 88%
“…Seno et al ( 2010b ) examined effects of stimulus color by manipulating the color of expanding optical flows and a background. In their study, the color of the dots and background were either red or green, and the dots were equiluminant.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, vection has been linked to visually induced MS (Hettinger, Berbaum, Kennedy, Dunlap, & Nolan, 1990;McCauley & Sharkey, 1992); and may be a precondition for visually induced MS (Crampton & Young, 1953;Smart, Stoffregen, & Bardy, 2002), as most users of virtual simulators who report sickness also experience vection (Hettinger et al). Vection itself is determined by a number of other factors, such as the participant's field of view (Brandt, Dichgans, & Koenig, 1973;IJsselsteijn, de Ridder, Freeman, Avons, & Bouwhuis, 2001) or even the color of the visual stimulus (Bonato & Bubka, 2006;Seno, Sunaga, & Ito, 2010). Apart from the role of the field of view, only a few studies have investigated the relationship between stereopsis and vection and found heterogeneous results.…”
Section: Introductionmentioning
confidence: 99%